Sens-ation: a service-oriented platform for developing sensor-based infrastructures. (9th May 2006) - Gross, Tom; Egla, Tareg; Marquardt, Nicolai
Context-aware systems use sensors in order to analyse their environment and to adapt their behaviour. We have designed and developed Sens-ation, an open and generic service-oriented platform, which provides powerful, yet easy-to-use, tools to software developers who want to develop context-aware, sensor-based infrastructures. The service-oriented paradigm of Sens-ation enables standardised communication within individual infrastructures, between infrastructures and their sensors, but also among distributed infrastructures. On a whole, Sens-ation facilitates the development allowing developers to concentrate on the semantics of their infrastructures, and to develop innovative concepts and implementations of context-aware systems.